ESG performance and debt financing cost - SHI, Bo (Institutional Knowledge at Singapore Management University, 2024)
Using the Latent Dirichlet Allocation thematic model, I calculate the comprehensiveness score of corporate ESG report and examine how the score correlates with corporate debt financing cost. Based on the empirical analysis over a sample of Chinese listed A-share firms with available ESG reports. I find that more comprehensive ESG report reduces corporate debt financing cost. Specifically, an increase by one standard deviation in ESG report comprehensiveness can decrease corporate debt financing cost by 3.88%. In heterogenous analysis, I find that the effect of ESG input on reducing corporate debt cost is stronger for state-owned firms. Good financial performance of firms can strengthen the effect of ESG report comprehensiveness on reducing corporate debt financing cost. Compared with firms processing more tangible assets, ESG report comprehensiveness plays a more valuable role in reducing debt cost for firms with more intangible assets. Higher growth opportunities can substitute lower ESG report comprehensiveness of firms. In further analysis, I find that ESG report comprehensiveness reduces corporate debt financing cost both through decreasing the interest rate of bank loans and enlarging the size of trade credit provided by suppliers. Different types of ESG input have differentiated effects on reducing corporate debt cost. The G (Governance) pillar of ESG has the most prominent effect on corporate debt financing cost, followed by the effect of the E (environmental) pillar, while the S (social) pillar has the least influence on reducing corporate debt financing cost. Different types of debt holders share common ESG concerns but also differ in the sensitivity to some risk related with different ESG pillars. Both banks and suppliers care about corporate governance related ESG risk. At the same time, banks pay more attention to corporate environmental performance while suppliers focus more on firm’s performance related with social issues.